The Effect of Industry 4.0 on the Development of Micro, Small and Medium Enterprises (MSMEs) Banana Chips in Bandar Lampung - Helmia Adita Fitra; Fran Sinatra (Jurnal Wilayah dan Lingkungan, 2020)
Industry 4.0 fosters the local economy to be globalized because of technological innovation and the use of the internet. In Indonesia, MSMEs play a vital role in determining national economic performance. In the era of industry 4.0, MSMEs in Indonesia must adopt the technological changes affected by Industry 4.0; otherwise, their business loses competitiveness in the future. To win the competitiveness in the era of industry 4.0, Banana chips MSMEs should formulate the strategies which address the technological improvement and innovation on the component of MSMEs development. This study aims to examine the effect of industry 4.0 on the aspects of MSMEs development, pervades production and infrastructure,  networking and financing support, sales and marketing, and human resources. This study used a quantitative approach and conducted a regression analysis to discover which aspect is affected by Industry 4.0. The results of the study revealed that only two components of Banana Chips MSMEs development affected industry 4.0. They are the component of sales and marketing and human resources components.